A hermeneutic study of cultural codes in English and Uzbek online health and education news - Kamola Tursunovna, Alimova (The Lingua Spectrum, 2026)
This article examines implicit cultural meanings in English and Uzbek online news headlines on health and education through a hermeneutic lens. The study treats the headline not as a neutral label but as a condensed interpretive act that organizes public attention, value, and responsibility. The pilot corpus consists of eight headlines from The Guardian, Gazeta.uz, and Daryo.uz published between 2023 and 2026. The analysis moves between lexical choice, agency patterns, evaluative framing, and broader cultural horizons of interpretation. The findings suggest that the English headlines in the sample more often foreground social tension, evidence, vulnerability, and policy contestation, while the Uzbek headlines more often foreground institutional initiative, procedural order, and collective welfare. The article argues that these differences do not reveal fixed national essences; rather, they point to recurring editorial preferences shaped by media culture, public discourse, and communicative expectations. The study contributes to comparative media linguistics by showing how cultural meanings often reside in what the headline presupposes rather than explicitly states.